Plant cathepsin B, a versatile protease - Coppola, Marianna; Mach, Lukas; Gallois, Patrick (Frontiers in Plant Science, 2024)
Plant proteases are essential enzymes that play key roles during crucial phases of plant life. Some proteases are mainly involved in general protein turnover and recycle amino acids for protein synthesis. Other proteases are involved in cell signalling, cleave specific substrates and are key players during important genetically controlled molecular processes. Cathepsin B is a cysteine protease that can do both because of its exopeptidase and endopeptidase activities. Animal cathepsin B has been investigated for many years, and much is known about its mode of action and substrate preferences, but much remains to be discovered about this potent protease in plants. Cathepsin B is involved in plant development, germination, senescence, microspore embryogenesis, pathogen defence and responses to abiotic stress, including programmed cell death. This review discusses the structural features, the activity of the enzyme and the differences between the plant and animal forms. We discuss its maturation and subcellular localisation and provide a detailed overview of the involvement of cathepsin B in important plant life processes. A greater understanding of the cell signalling processes involving cathepsin B is needed for applied discoveries in plant biotechnology.